(untitled) (Conferencea, 2022)
Humans and other complex multicellular organisms have organ systems that work together to carry out processes important to keeping the body alive. The human body has hierarchical structures built upon each other. Cells make up tissues, tissues make up organs, and organs make up organ systems. The functioning of the organ system depends on the coordinated activity of the organs that are part of it.